Collages and Reliefs 1910-1945 and Hiller-Heliographs - Beckett, Jane; Hiller, Karol; Nakov, Andrei Boris (London : Annely Juda Fine Art, 1982)
Andreenko, Michel ; Arp, Hans (Jean) ; Balla, Giacomo ; Bergmann-Michel, Ella ; Berlewi, Henryk ; Buchheister, Carl ; Buchholz, Erich ; Domela, César ; Ermilov, Vassily ; Ernst, Max ; Exter, Alexandra ; Gabo, Naum ; Hausmann, Raoul ; Höch, Hannah ; Joostens, Paul ; Kliun, Ivan ; Laurens, Henri ; Lissitzky, El ; Michel, Robert ; Moholy-Nagy, Laszlo ; Péri, László ; Pevsner, Antoine ; Picasso, Pablo ; Popova, Liubov ; Schwitters, Kurt ; Suetin, Nikolay ; Tatlin, Vladimir ; Vordemberge-Gildewart, Friedrich
biog. per kunstenaar
Engels
Collages and Reliefs 1910-1945 and Hiller-Heliographs, Annely Juda Fine Art, London, 30 June - 2 October, 1982
boek